Operational Evaluation of the Document and Archive Management Application at Disdukcapil Salatiga using the EUCS Method (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Efficient population administration services require information systems that effectively support staff performance. This study aims to evaluate user satisfaction with the internal application used by the Salatiga Civil Registry Office (Disdukcapil) using the End User Computing Satisfaction (EUCS) method. Data were collected through questionnaires distributed to 10 respondents from two different job functions (service counter and archive), and analysed using descriptive statistics and the Mann-Whitney test. The results show that user satisfaction scores were generally high (ranging from 3.9 to 4.3), with no statistically significant differences in perceptions based on job function or duration of system use (p > 0.05). This suggests that the application is widely accepted among users. However, limitations such as a small sample size and lack of personalised features may affect the generalizability of the findings. The study recommends improving interface design and increasing system flexibility to better align with operational needs. Future research should involve a larger number of respondents and consider evaluating additional technical aspects, such as data security and system integration.